Prevalence of the Hypertriglyceridemic Waist Phenotype: Results from the Second Measurement of the CARMEN Initiative - Alain Francisco Morejón Giraldoni; Eloida Rivas Alpízar; Verónica Salas García; Mikhail Benet Rodríguez (Revista Finlay, 2014)
Background: the hypertriglyceridemic waist phenotype is associated with other cardiometabolic disorders and is considered a predictor of diabetes mellitus. In Cuba, its prevalence is not clearly known. Objective: to describe the prevalence of the hypertriglyceridemic waist phenotype in the municipality of Cienfuegos. Methods: a cross-sectional study was conducted with an equal-probability sample stratified by age group and sex during 2010 and 2011. The sample consisted of 1108 patients aged 15 to 74 years from the municipality of Cienfuegos. The variables analyzed were: sex, age, skin color, waist circumference, triglyceride levels and hypertriglyceridemic waist phenotype. Data are presented in tables and figures using absolute and relative frequencies. An analysis of the prevalence rates adjusted for age group and sex was performed. Results: prevalence of the hypertriglyceridemic waist phenotype was determined in 14.4 % of the study population. Women and white skin patients predominated, accounting for 17.3 % of the total population. The components of the phenotype show differences, hypertriglyceridemia is more common in males and all age groups (40.2 %) while obesity measured by waist circumference predominates in women (33.4 %). Conclusions: women have a higher risk of developing hypertriglyceridemic waist phenotype given the increased presence of obesity measured by waist circumference and elevated serum triglyceride level in all age groups, particularly in those over 45 years. This represents a significant cardiometabolic risk that requires preventive approaches.